Transcriptional co-regulator OCA-B/Pou2af1 restricts Th2 differentiation - Hughes, Erik P.; Manna, Asit K.; Sun, Wenxiang; Osburn-Staker, Sandra M.; Aamodt, Samuel; Warren, Kristi J.; Cox, James E.; Tantin, Dean (Frontiers in Immunology, 2025)
BackgroundType 2 immunity is initiated through a synergistic response between innate and adaptive immune cells to facilitate host-pathogen defense and wound repair, yet aberrant responses can contribute to chronic inflammation and allergic disease. CD4+ type 2 helper T (Th2) cells facilitate the adaptive immune response through the secretion of cytokines such as IL-4, IL-5, and IL-13. While the Th2 program is governed by the transcription factor GATA3, less is known about regulators that fine-tune the Th2 cytokine response.MethodWe used a proximity labeling system to map proteins associated with the transcriptional co-regulator OCA-B, encoded by Pou2af1, in T cells. We used a series of genomic, biochemical and immunological assays to probe the interaction with one particular hit from the screen.ResultsWe find that OCA-B indirectly associates with GATA3. ChIP-seq analysis reveals coenrichment of Gata3 and the transcription factor Oct1, a partner protein of OCA-B, at genomic locations responsible for the Th2 program including Il4, Il13, Il5, Gata3, and Irf4. DNA binding data using recombinant proteins and reporter data using T cell lines are consistent with a model in which OCA-B restricts transcription at the Th2 locus control region and subsequent IL-4 and IL-13 secretion. Finally, in an in vivo papain allergy model we show OCA-B expression in T cells limits the frequency of T cells within the lung.ConclusionThese findings shown that OCA-B helps restrict Th2 function at least in part through communication with GATA3.